Extent of Larval Populations of Turfgrass Insect Pests at Rocky Ford Turfgrass Research Center at Manhattan, KS - Raymond A. Cloyd (Kansas Agricultural Experiment Station Research Reports, 2018)
Many insect pests have a larval or grub stage that resides belowground and feeds on turfgrass roots (Potter, 1998; Vittum et al., 1999; Held and Potter, 2012). The major belowground insect pests (white grubs) associated with turfgrass throughout Midwestern states that are present in Kansas include: May/June beetles (Phyllophagaspp), masked chafers (Cyclocephalaspp), and bluegrass billbug (Sphenophorus parvulus) (Miller et al., 2013). However, there is limited information on the annual occurrence of these insect pests affiliated with the common turfgrass species planted in Kansas, including zoysiagrass (Zoysia japonica) and Kentucky bluegrass (Poa pratensis). Therefore, the objective of this study was to determine the extent of larval populations of the major belowground insect pests of Kansas throughout the growing season.
Keywords: insect pests; monitoring; abundance; larvae